Identifying tourism and economic growth nexus the hurlin venet approach - ÇAĞLAYAN AKAY, EBRU; ŞAK, NAZAN (My University, 2013)
This paper seeks to identify causality between tourism and economic growth within Hurlin-Venet approach using the panel data of 135 countries for the period 1995–2008. Countries are classified by income levels. The unidirectional causality from economic growth to tourism revenue is found only in case of high income countries group.
Keywords: Sosyal ve Beşeri Bilimler; Ekonometri; Social Sciences and Humanities; Econometrics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; ourism Income; Economic Growth; Panel Unit Root; Panel Causality